ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS PENGARUHNYA TERHADAP KINERJA KEUANGAN PT POS INDONESIA (PERSERO) - Galuh Ajinugraha (Scientia Regendi, 2020)
PT Pos Indonesia (Persero) is a state-owned enterprise founded in 1906 with initial objective was to provide the delivery of mail and package service. PT Pos Indonesia (Persero) monopolized that industry until 1995 but underwent decline mainly because the emergence of it’s competitors which utilized the advancement of IT faster. The loss of PT Pos Indonesia (Persero) against it’s competitors have many reasons, mainly from management side. This research is meant to prove it by observing from the financial aspect and also searching for other factors which influencing that phenomena. Thus the writer formulized the following problems : What is the influence of Liquidity, Solvency, and Activity to Financial Performance be it partially or simultaneously and the purpose of the research is to determine the influence of Liquidity, Solvency, and Activity to Financial Performance be it partially or simultaneously. This research is categorized as Descriptive Quantitative with two data sources which are primary data from interview with Accounting Manager and Accounting Management of PT Pos Indonesia (Persero) and secondary data from financial reports and their restatements from 2008-2016. The method of data analysis is Path Analysis and statistical calculation was done with SPSS ver.24. The result of the research discovered that Liquidity has positive influence to Financial Performance, Solvency has negative influence to Financial Performance, Activity has positive influence to Financial Performance, and simultaneously Liquidity, Solvency, and Activity have positive influence to Financial Performance.